Complementary and alternative medicine use in migraine patients: results from a national patient e-survey - Makarevičius, Gytis; Dapkutė, Austėja; Ryliškienė, Kristina (Frontiers in Neurology, 2024)
Object This cross-sectional study aims to investigate migraineurs’ preferred complementary and alternative medicine (CAM) types and the factors influencing their usage. Materials and methods An anonymous e-survey was distributed to Lithuanian Migraine Association members, and social media migraine support communities. The collected data consisted of demographic, migraine-related questions, personal qualities, CAM habits. Results 470 respondents were analyzed. 95.96% were women with a median age of 37 (IQR 31, 44). The median duration of migraine was 17.5 years (IQR 10, 25) and the median headache severity was rated 8 (IQR 7, 10) out of 10. 68.90% of participants had one or more headache days per week. 71.49% of respondents were triptan users, 27.66% used medical prophylaxis, and 17.87% used monoclonal antibodies. 52.55% of respondents used CAM in the past 12 months. Physical activity (36.17%), dietary changes/fasting (27.02%), relaxation/meditation (26.60%) were the most used CAM types. Reasons for CAM use included dissatisfaction with conventional treatment effectiveness (42.51%), concerns about safety (48.18%) and adverse effects (37.25%). Factors associated with the decision to explore CAM included longer headache duration (p = 0.017, Mann–Whitney U test), frequent sick leaves (p < 0.001, Mann–Whitney U test), current preventive medication use (p = 0.016, chi-square test), positive views on CAM safety/naturality (p = 0.001/ p < 0.001, Mann–Whitney U test), belief of having a healthy diet (p < 0.001, chi-square test), food-related worries (p = 0.011, Mann–Whitney U test) and Big-five personality trait of openness to experience (p = 0.049, chi-square test). After logistic regression, the frequent need to take sick leaves, having a healthy diet, food-associated fears maintained statistical significance. CAM use was not associated with non-adherence to conventional medicine. 48.99% of CAM consumers disclosed CAM use to their doctors. Conclusion CAM is explored by a significant proportion of migraineurs, less than half communicate this to their doctors. In our sample, physical activity, dietary changes, and relaxation techniques were the most common. Many patients opted for CAM due to previously experienced side effects/ineffectiveness of conventional migraine treatment or the fear of potential harm from standard medication. Individual factors, such as openness of personality can be an important contributing factor.